2015
DOI: 10.1017/jrr.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

A Dyadic Analysis of Power and Friendship Functioning

Abstract: This study explored how perceptions of resource control levels are related to perceptions of friendship functioning in late adolescent friendship dyads (92 female dyads, 43 male dyads; mean age = 19.59 years). Resource control, relationship influence, and positive and negative friendship features were determined using self- and friend-reports. Contrary to expectations, a latent actor-partner interdependence model (Olsen & Kenny, 2006) revealed uniformly positive effects of perceived resource control on fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…While not explicitly tied to reproduction per se, work on social dominance and related constructs has shown that dominant and resource controlling adolescents enjoy dating success (Pellegrini and Bartini 2001;Pellegrini and Long 2003;Volk et al 2014;Book et al 2012). From a resource control theoretic perspective, this would be hypothesized since resource controllers are resources in and of themselves (Stump et al 2015). Resource control theory, when applied to sexual fantasies about submitting to dominant partners, demonstrated that dominant partners are preferred by both sexes (Hawley and Hensley 2009).…”
Section: Methodology and Theory: Challenging Common Misconceptionsmentioning
confidence: 99%
“…While not explicitly tied to reproduction per se, work on social dominance and related constructs has shown that dominant and resource controlling adolescents enjoy dating success (Pellegrini and Bartini 2001;Pellegrini and Long 2003;Volk et al 2014;Book et al 2012). From a resource control theoretic perspective, this would be hypothesized since resource controllers are resources in and of themselves (Stump et al 2015). Resource control theory, when applied to sexual fantasies about submitting to dominant partners, demonstrated that dominant partners are preferred by both sexes (Hawley and Hensley 2009).…”
Section: Methodology and Theory: Challenging Common Misconceptionsmentioning
confidence: 99%